2020
DOI: 10.1039/d0cp00484g
|View full text |Cite|
|
Sign up to set email alerts
|

Salt parameterization can drastically affect the results from classical atomistic simulations of water desalination by MoS2 nanopores

Abstract: Water scarcity is a reality in our world, and scenarios predicted by leading scientists in this area indicate that it will worsen in the next decades. However, new technologies based in low-cost seawater desalination can prevent the worst scenarios, providing fresh water for humanity. With this goal, membranes based in nanoporous materials have been suggested in recent years. One of the materials suggested is MoS 2 , and classical Molecular Dynamics (MD) simulation is one of the most powerful tools to explore … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…We close by stressing that nagging problems may appear when using force fields to describe aqueous ion solutions in slit pores based on molecular dynamics simulations. For MoS 2 /graphene nanopore setups mimicking desalination devices, it has been found that both water permeability and salt rejection by the membrane are most sensitive to the parametrization of the ion model, especially for narrow pores, up to the point that qualitatively distinct mechanisms have been observed depending on the salt model …”
Section: Confinement Effects On Charge Defect Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…We close by stressing that nagging problems may appear when using force fields to describe aqueous ion solutions in slit pores based on molecular dynamics simulations. For MoS 2 /graphene nanopore setups mimicking desalination devices, it has been found that both water permeability and salt rejection by the membrane are most sensitive to the parametrization of the ion model, especially for narrow pores, up to the point that qualitatively distinct mechanisms have been observed depending on the salt model …”
Section: Confinement Effects On Charge Defect Migrationmentioning
confidence: 99%
“…For MoS 2 /graphene nanopore setups mimicking desalination devices, it has been found that both water permeability and salt rejection by the membrane are most sensitive to the parametrization of the ion model, especially for narrow pores, up to the point that qualitatively distinct mechanisms have been observed depending on the salt model. 161…”
Section: Confinement Effects On Charge Defect Migrationmentioning
confidence: 99%
“…MoS 2 has nanopores with 0.97 nm diameter (defined as the center to center distance of atoms), which is the minimum size that does not show the ion blockage effect. 18 The simulations were performed using the Large-scale Atomic/ Molecular Massively Parallel Simulator (LAMMPS). 37 The particles interact with each other via Lennard-Jones (LJ) and Coulomb potentials.…”
Section: Articlementioning
confidence: 99%
“…One suited simulation branch to better understand the desalination process is to mimic the reverse osmosis desalination system at the nanoscale. [8][9][10][11][12][13][14][15][16][17][18][19][20] This technique enters in the scope of Non-Equilibrium Molecular Dynamics (NEMD). In addition, its procedure has been used to get insights into designing new membrane materials for desalination.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the interactions between unlike atoms in the system, geometric mean combining rules, σ ij = (σ i σ j ) 1/2 and ε ij = (ε i ε j ) 1/2 , were used, where σ represents the distance at which the interatomic LJ potential is zero and ε represents the LJ well-depth parameter. In Section S4, we present a more detailed discussion on the choice of force fields for hBN, water molecules, and salt ions (see, e.g., refs and ).…”
Section: Methodsmentioning
confidence: 99%